2011
DOI: 10.1111/j.1528-1167.2011.03042.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms in Norwegian children with epilepsy aged 8-13 years: Effects of age and gender?

Abstract: SUMMARYPurpose: In this population-based study we wanted to assess the prevalence and impact of psychiatric symptoms in children with epilepsy compared to controls, and investigate possible age and gender differences. Methods: Data were collected using the Strengths and Difficulties Questionnaire-Parent report (SDQ-P) as part of a more extensive questionnaire. A total of 14,699 parents of children aged 8-13 years (response rate 78%) participated. Associations between SDQ scores and epilepsy, other chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 40 publications
6
35
0
1
Order By: Relevance
“…2006; Alfstad et al. 2011), and could be associated. Furthermore, fear of fetal malformations as a consequence of AED use during pregnancy, fear of seizures during pregnancy, and fear of the risk of epilepsy in the child may also be potentially contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Alfstad et al. 2011), and could be associated. Furthermore, fear of fetal malformations as a consequence of AED use during pregnancy, fear of seizures during pregnancy, and fear of the risk of epilepsy in the child may also be potentially contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…2006; Alfstad et al. 2011). A Norwegian study suggested that young adults with epilepsy are more prone to risk‐taking behavior, discussing whether epilepsy may be an independent risk factor for early sexual debut (Alfstad et al.…”
Section: Discussionmentioning
confidence: 99%
“…2 Beyond seizures, children with epilepsy (CWE) face numerous challenges including a high burden of psychiatric and behavioral comorbidities that often go untreated or even unrecognized. [3][4][5][6][7][8][9][10] Such comorbidity might predate the onset of epilepsy or persist in the setting of seizure remission, thereby suggesting that epilepsy is a pervasive condition encompassing more than seizures. 11,12 The observation that CWE, many of whom are in remission, have poor psychosocial outcomes as adults with respect to employment, educational attainment, socioeconomic status, and quality of life, highlights the pervasiveness of epilepsy's health impacts and suggests that factors not related to seizures might have an impact on psychosocial outcomes, including HRQoL.…”
mentioning
confidence: 99%
“…Children with epilepsy are at significantly higher risk for a range of behavioral and psychiatric disorders including attention deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), depressive and anxiety disorders. Although psychiatric disorders are frequently seen in patients with epilepsy, these disorders usually have been undiagnosed or untreated [3][4][5][6][7] . It has been found that at most only one third of the patients with mental disorders receive psychiatric treatment 6,7 .…”
mentioning
confidence: 99%
“…Although psychiatric disorders are frequently seen in patients with epilepsy, these disorders usually have been undiagnosed or untreated [3][4][5][6][7] . It has been found that at most only one third of the patients with mental disorders receive psychiatric treatment 6,7 . Family members of children with a chronic disease are severely affected by the stress caused by this disease.…”
mentioning
confidence: 99%